Acteurs et enjeux de la transhumance dans la forêt classée de l’Alibori Supérieur au nord du Bénin (Afrique de l’Ouest) - Alassan Assani Seidou; Hilaire Sanni Worogo; Brice Assogba; Mohamed Nasser Baco; Ibrahim Alkoiret Traore; Marcel Houinato (VertigO, 2023)
The transhumant herding system is increasingly dependent on protected areas to escape the scarcity of grazing areas, the occupation of transhumance corridors, the inadequacy of land legislation and the numerous social problems (human and material damages) in the sub-region and in Benin in particular. The present study was carried out in the villages bordering the Alibori Supérieur classified forest (FC-AS), a reception area for national and foreign transhumant herders in northern Benin. The study aims to characterize the stakeholders and analyze the issues involved in transhumance for the sustainable exploitation of pastoral resources in this protected area. Data was collected through the surveys of 300 transhumance stakeholders in nine villages bordering this classified forest. Nine focus groups and semi-structured interviews were also carried out with 36 resource persons (administrative services, traditional chiefs, various associations) involved in transhumance management. The results showed that several actors interact in the management of transhumance and pastoral resources in FC-AS. These actors were grouped into two categories. These are those who regulate access to resources (administrative authorities, traditional chiefs, various associations, and so on); and those who compete for access to resources (herders, farmers, loggers, et cetera). For the former, the stakes are often identity and legitimacy, while for the latter, they are economic, characterized by alliances alternating with conflicts. All the players surveyed have concerns that vary according to the constraints linked to the exploitation of these resources. These include the development and securing of pastoral resources for 70,4% of herders surveyed, the creation of a cultivation zone for the majority of farmers (83,6%), compliance with texts and laws relating to transhumance (47,4% of agents of deconcentrated services), herder awareness-raising (56,6% of NGOs and associations) on how to conduct themselves with regard to transhumance and peaceful transhumance (79,1% of the traditional chiefs). For sustainable use of pastoral resources in protected areas by stakeholders, their concerns must be taken into account in the process of implementing forest management plans.